2021
DOI: 10.1038/s41598-021-02358-0
|View full text |Cite
|
Sign up to set email alerts
|

Early operative morbidity in 184 cases of anterior vertebral body tethering

Abstract: Fusion is the current standard of care for AIS. Anterior vertebral body tethering (AVBT) is a motion-sparing alternative gaining interest. As a novel procedure, there is a paucity of literature on safety. Here, we report 90-day complication rates in 184 patients who underwent AVBT by a single surgeon. Patients were retrospectively reviewed. Approaches included 71 thoracic, 45 thoracolumbar, 68 double. Major complications were those requiring readmittance or reoperation, prolonged use of invasive materials such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…As VBT requires an intrathoracic access with lung deflation, the use of an intrathoracic drain is necessary to prevent the development of secondary pneumothorax and pleural effusion. Nonetheless, pulmonary complications are not infrequent and occur in 7–10% of patients [ 1 5 ]. While recent studies have showed that the short-term lung function is not affected by the development of these complications [ 6 , 7 ], there is an ongoing effort toward identifying their possible risk factors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As VBT requires an intrathoracic access with lung deflation, the use of an intrathoracic drain is necessary to prevent the development of secondary pneumothorax and pleural effusion. Nonetheless, pulmonary complications are not infrequent and occur in 7–10% of patients [ 1 5 ]. While recent studies have showed that the short-term lung function is not affected by the development of these complications [ 6 , 7 ], there is an ongoing effort toward identifying their possible risk factors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Spine flexibility and motion are maintained. 2,3 Early studies have demonstrated effective deformity correction-up to 71%-the complication rate was not trivial; 1,[4][5][6][7] the reoperation rate ranges from 3% to 24%. 1,2,5,6 Some reoperations involve the release of the tether secondary to overcorrection.…”
mentioning
confidence: 99%
“…Few studies, however, have compared AVBT and IPSF with respect to perioperative outcomes, which is a potential area where AVBT patients can derive the greatest benefit 5,10,11,16,17. Newton et al5 compared perioperative metrics for AVBT and IPSF, reporting increased surgical time and blood loss in patients undergoing IPSF.…”
mentioning
confidence: 99%